Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan Pada PT Indomarco Prismatama Cabang Tangerang 1 - Santi Susanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
Human Resource Management (HRM) plays a crucial role in ensuring that a company is able to grow, compete, and sustain its operations in an increasingly dynamic business environment. Effective HRM practices help organizations optimize employee performance, improve productivity, and maintain workforce stability. One of the key aspects of HRM that significantly influences employee performance is workload and job satisfaction. An imbalance in workload or low levels of job satisfaction may lead to decreased motivation, stress, and reduced work performance. This research aims to explore and evaluate the levels of workload and job satisfaction among employees at PT Indomarco Tangerang 1. Understanding these factors is essential to identify potential problems that may affect employee performance and organizational effectiveness. The study employs a quantitative research approach, which involves collecting numerical data that can be statistically analyzed to provide objective and measurable results. Data were gathered through structured questionnaires distributed to employees. A total of 30 employees from various divisions at PT Indomarco Tangerang 1 participated in this study. Statistical analysis was used to assess the relationship between workload and job satisfaction, as well as their overall condition within the company. The findings of this research are expected to provide useful insights for management in developing appropriate strategies to manage workload effectively and enhance job satisfaction. Ultimately, improving these aspects is expected to contribute to higher employee performance and support the long-term success of the company.